Adsorption isotherms and kinetics of vanadium by shale and coal waste - George William Kajjumba; Serdar Aydın; Sinan Güneysu (Adsorption Science & Technology, 2018)
The use of adsorption using nanomaterials has become a very competitive method for removal of hazardous materials from wastewater. With increasing consumption of fossil fuels and development of energy storage systems, the levels of vanadium pollution are expected to increase. Utilizing natural shale and coal waste as adsorbents, batch adsorption, isotherms, and kinetics of vanadium was studied. The adsorption characteristics of shale and coal waste were studied using Fourier Transform Infrared spectroscope and Scanning Electron Microscopy. The effect of pH, the amount of adsorbent, vanadium concentration, temperature, and contact time between adsorbate and adsorbents were also studied to obtain optimum conditions for maximum adsorption of vanadium. The Fourier Transform Infrared results show little distortion in the vibration of bands, and hence the surface properties remain unchanged for both sorbents after adsorption. The adsorption kinetics are best described by pseudo-second order, while Langmuir model fits the adsorption isotherm for both adsorbents. Maximum sorption capacity is 67.57 mg/g for shale while that of coal is 59.88 mg/g at 298 K and pH 3. For both adsorbents, the adsorption process is spontaneous, endothermic, and chemisorption in nature. Both adsorbents can effectively be recycled twice.